Pengaruh Pertumbuhan Ekonomi Dan Pengangguran Terbuka Terhadap Kemiskinan Di Indonesia Tahun 2001-2021 - Feliks Arfid Guampe; Abdi Sakti Walenta; Fredrik Bastian Kawani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This study aims to measure the influence of economic growth and opened unemployment on poverty in Indonesia by using the data of 2001-2021. The method of data analysis used multiple regression by using SPSS 26. The result of this study showed that the economic growth has positive and insignificant influence on poverty. On the other hand, opened unemployment has positive and significant influence on the level of poverty where the value of t-count 8.033 t-table 2.10982 with the probability value 0.000 0,05. Simultaneously, the level of economic growth and opened unemployment has a significant influence on the level of poverty. The value of coefficient determination showed that the economic growth and opened unemployment are able to explain poverty by 75,6% while 24,4% is explained by other variables outside of this study.